Exposure to tobacco smoke among pupils from Sopot primary schools. SOPKARD study results. (30th September 2020) - Balwicki, Ł; Tyrańska-Fobke, A; Suligowska, K L; Zdrojewski, T
Abstract: Background: The problem of tobacco use among minors and in their immediate environment remains a significant challenge in Poland. Although Poland has passed smoke free law children are still being exposed to tobacco smoke. The purpose of this study was to analyze the phenomenon of tobacco use by children in City of Sopot and in their surroundings. Methods: The cross-sectional study was conducted as part of the SOPKARD program for early detection of risk factors for civilization diseases in children and adolescents. A limited GYTS questionnaire was utilized to conduct the study. Data was collected from all the fifth grade students (9-11 yo) attending to Sopot primary schools in 2017 and 2018. Results: The study involved 385 students (161 in 2017 and 224 in 2018). Only few students tried to smoke traditional cigarettes (3%) or use electronic e-cigarettes (2%). Despite the legal ban, 24% of students saw smokers in the school premises. In addition, 34% of children said that one or both of their parents smokes and that in only slightly more than ¾ of the houses smoking is completely prohibited. As many as 66% of students reported smoking incidents in the cars they travel. There were 16% students who think they could start smoking in the future. Conclusions: The results suggest that Sopot children are still exposed to tobacco smoke inhalation. It happens in private, non-smoking areas (homes and family cars). It is worth conducting educational activities and considering legislative initiatives such as smoking ban in vehicles carrying children to stimulate parents to take care more of the health of their children. Key messages: Although tobacco legislation in Poland protects people from passive smoking in public places children are still exposed in private premises. Ban on smoking should be extended to privates cars at minimum.